Aspek Islam dalam Turisme Kolonial di Jawa - Sunjayadi, Achmad (UI Scholars Hub, 2010)
Despite some vital and interwoven cultural elements of the colonial Dutch East-Indies, the existence of Islam has never been brought up as part of the local culture. Since Islam in the colony was perceived with prejudice, the colonial government considered that it was not important to mark the contribution of Islam in the culture of the Indies. The paper reveals that there has been little information published by the colonial travel bureau on the Islamic spiritual aspects, despite the fact that there were some records written by foreign tourists who were interested in the practice of Islam. The tourist bureau favored Islamic architecture and featured the Hindu influence on Islam